A educação infantil como um direito social da criança : uma análise sobre a prática docente a partir da implementação das Diretrizes Curriculares Nacionais para a Educação Infantil no município de Sinop-MT - Ferreira, Sandra da Conceição Donato (2019)
This work was developed in the Postgraduate Program in Education (PPGEdu) of the Institute of Human and Social Sciences (ICHS) of the Federal University of Mato Grosso - University Campus of Rondonópolis (UFMT / CUR). What moves us, in this research, is to reflect if there were changes in teaching practices from the process of implementation of the National Curriculum Guidelines for Early Childhood Education (DCNEI), at municipal level (2012- 2018), in Sinop, Mato Grosso. The municipality has been implementing a municipal policy that seeks to establish a relationship between theory and practice in the work carried out, which requires a critical reflection. The general objective of this research is to investigate if there was any change in teaching practices from the DCNEI implementation process (BRASIL, 2010) at the municipal level. The specific objectives are: To analyze how the Municipal Directive contemplates the DCNEI (2010); To understand how the Municipal Direction has contributed to the implementation of pedagogical proposals in the daily life of the institutions of Early Childhood Education; To investigate the knowledge and understanding that the collective of professionals has about pedagogical proposal and teaching practice; Propose, from the analyzed result, along with the people participating in the research, suggestions for improvement for the teaching-learning process with public administration of the municipality. The interest in this topic has origin from my work in the coordination of the municipal network of Early Childhood Education, where a work was carried out in the municipality in partnership with the Ministry of Education (MEC), on the Pedagogical Political Plan / Pedagogical Policy Proposal (PPPM) or Municipal Guideline for Early Childhood Education. This research is of Communicative Research, an approach developed by the Special Center for Research on Theories and Practices Overcoming Inequalities (CREA) - University of Barcelona (UB / ES) and whose theoretical basis is the studies of Jürgen Habermas and Paulo Freire. This type of research seeks to break with the roles of division between the researcher and the research participants, being a joint and humane construction of the whole process, which allows both reflection and analysis of the information collected, setting up a transformation result of the situation investigated. We consider the final analyzes relevant to the research, since the themes presented show that there are advances. However, some particularities regarding the work that is proposed for the Curricular Guidelines, regarding the pedagogical practice, that is, in the integration of curricular contents, aiming at the learning teaching process with the play. The data show that the group of teachers performs their classes in different ways, but there is still a lack of understanding regarding the proposal of the DCNEI, which focus on the child, for the formation of critical citizens, and is therefore not a proposal that thinks and defines the teacher as the center of the teaching and learning process. Studies are needed to conduct this process - which is as complex as possible and necessary - in order to understand what the role of the teacher is not only in the school, but in today's society. Therefore, a dialogue must become urgent for the transformation to take place, the political engagement of struggle has to be permanent, if the teacher is not part of this process, there is no commitment. Thereby, we agree with Freire (2015) that we must take a stand in front of our social responsibility, to participate in the transformation process of the school, knowing the importance of teaching and learning in a harmonious, respectful and committed way through educational practices that promote the equality, since the good result of the learning takes place in the relations contained in the act of teaching and in the commitment to the learning.